2023
DOI: 10.1111/jphd.12561
|View full text |Cite
|
Sign up to set email alerts
|

Trends in dental insurance claims in the United States in the context of the COVID‐19 pandemic: A 3‐year perspective (2019–2022)

Abstract: Objectives: We showed in a previous analysis the patterns of disruption for private dental insurance claims in the United States caused by the SARS-CoV-2 pandemic in 2020. The present report examines trends during 2020 and 2021, that is, contrasting perspectives during 2019 with the acute phase of the pandemic in 2020, and 2021. Methods: Private dental insurance paid claims from a data warehouse were obtained, encompassing a 5% random sample of records between January 2019 and December 2021 for child and adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…In this study, we found a large decline in dental care utilization across all age groups during the initial wave of the COVID-19 pandemic. Similar changes in dental care utilization during the lockdown or emergency state under the COVID-19 pandemic were also reported in the previous studies conducted in Japan, 10,19 the United States, 6,8 and Canada. 9 They also reported that the decline in dental care utilization immediately recovered to the previous level.…”
Section: Possible Explanation Of the Present Findingssupporting
confidence: 85%
See 1 more Smart Citation
“…In this study, we found a large decline in dental care utilization across all age groups during the initial wave of the COVID-19 pandemic. Similar changes in dental care utilization during the lockdown or emergency state under the COVID-19 pandemic were also reported in the previous studies conducted in Japan, 10,19 the United States, 6,8 and Canada. 9 They also reported that the decline in dental care utilization immediately recovered to the previous level.…”
Section: Possible Explanation Of the Present Findingssupporting
confidence: 85%
“…5 Previous studies reported dental visit avoidance during the COVID-19 pandemic periods. [6][7][8][9] Research conducted in Japan reported that the decrease in dental visits was limited to the short term after the outbreak. 10 Although the avoidance of dental visits is considered to differ according to the patient's susceptibility to Sars-CoV-2 infection (i.e., age or comorbidity), few previous studies have investigated the heterogeneity of dental visit avoidance during the COVID-19 pandemic by the patients' characteristics.…”
Section: Introductionmentioning
confidence: 99%